Left–right asymmetry: cilia stir up new surprises in the node. Issue 5 (May 2013) - Babu, Deepak; Roy, Sudipto
Abstract : Cilia are microtubule-based hair-like organelles that project from the surface of most eukaryotic cells. They play critical roles in cellular motility, fluid transport and a variety of signal transduction pathways. While we have a good appreciation of the mechanisms of ciliary biogenesis and the details of their structure, many of their functions demand a more lucid understanding. One such function, which remains as intriguing as the time when it was first discovered, is how beating cilia in the node drive the establishment of left–right asymmetry in the vertebrate embryo. The bone of contention has been the two schools of thought that have been put forth to explain this phenomenon. While the 'morphogen hypothesis' believes that ciliary motility is responsible for the transport of a morphogen preferentially to the left side, the 'two-cilia model' posits that the motile cilia generate a leftward-directed fluid flow that is somehow sensed by the immotile sensory cilia on the periphery of the node. Recent studies with the mouse embryo argue in favour of the latter scenario. Yet this principle may not be generally conserved in other vertebrates that use nodal flow to specify their left–right axis. Work with the teleost fish medaka raises the tantalizing possibility that motility as well as sensory functions of the nodal cilia could be residing within the same organelle. In the end, how ciliary signalling is transmitted to institute asymmetric gene expression that ultimately induces asymmetric organogenesis remains unresolved.